New trends and Opportunities for the Integrated Development of China's Sports Finance and Sports Industry - Chen, Lianlian; Pu, Baosheng (International Journal of Global Economics and Management, 2024)
The integrated development of China's sports finance and sports industry is ushering in new trends and opportunities. With the continuous growth of China's economy and the improvement of residents' living standards, the sports industry, as an important part of the national economy, is ushering in unprecedented development opportunities. As a key force to support the development of the sports industry, the necessity of sports finance is becoming increasingly prominent. The driving role of national policies cannot be ignored, and a series of policies are aimed at promoting the deep integration of the sports industry and the financial sector. The innovation of sports financial products and services, such as the development and application of sports insurance products, the innovation of sports credit and investment products, and the development prospects of sports financial derivatives, have provided new financing methods and investment channels for the sports industry. The integration model of sports finance and sports industry, including sports event financing and sponsorship model, financial support for stadiums and infrastructure, and financial management of sports clubs and athletes, has injected new vitality into the sustainable development of the sports industry. The risk management and control of sports finance, as well as the construction of a regulatory framework for sports finance, are the key to ensuring the stable development of the sports finance market. The impact of technological progress on sports finance, the long-term trend of the integration of sports finance and sports industry, and the opportunities and challenges of sports finance in the context of globalization are all important aspects of the future development of sports finance.